2018
DOI: 10.1002/2017tc004793
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Comment by Vincent et al.

Abstract: Key Points The Greater Caucasus Basin encompassed a broader region than envisioned by Vincent et al., who disregard Cenozoic shortening Terminal basin closure occurred when the Greater and Lesser Caucasus collided Data cited by Vincent et al. document the onset of basin closure by 35 Ma, but do not indicate terminal basin closure at this time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…In the Kazbegi region of Georgia (Figure ), several early studies place the MCT along the Adaykom‐Kazbek (or Adaykomskiy) fault, which broadly juxtaposes the crystalline Gveleti and Dariali massifs to the north against Caucasus Basin strata to the south (Leonov, ; Shempelev, ), whereas other studies place the MCT on the Tiba fault ~20 km to the south (e.g., Rogozhin et al, ; Vincent et al, ). Likewise, the location of the MCT is also disputed within the Caucasus Basin strata in eastern Greater Caucasus, with some authors placing it within the main range (e.g., Mosar et al, ; Vincent et al, ) and others on the Zangi fault farther to the south, at a major structural juxtaposition of differing Cretaceous facies (Cowgill et al, ; Forte et al, ; Khain et al, ; Kopp & Shcherba, ). In the western Greater Caucasus, the MCT footwall comprises either the Dizi series or Caucasus Basin strata, depending on location.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…In the Kazbegi region of Georgia (Figure ), several early studies place the MCT along the Adaykom‐Kazbek (or Adaykomskiy) fault, which broadly juxtaposes the crystalline Gveleti and Dariali massifs to the north against Caucasus Basin strata to the south (Leonov, ; Shempelev, ), whereas other studies place the MCT on the Tiba fault ~20 km to the south (e.g., Rogozhin et al, ; Vincent et al, ). Likewise, the location of the MCT is also disputed within the Caucasus Basin strata in eastern Greater Caucasus, with some authors placing it within the main range (e.g., Mosar et al, ; Vincent et al, ) and others on the Zangi fault farther to the south, at a major structural juxtaposition of differing Cretaceous facies (Cowgill et al, ; Forte et al, ; Khain et al, ; Kopp & Shcherba, ). In the western Greater Caucasus, the MCT footwall comprises either the Dizi series or Caucasus Basin strata, depending on location.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…However, Vincent et al (2018) argued that at least within the western Greater Caucasus, sedimentological, provenance, and seismic data supports an earlier basin closure age in Early Oligocene. Cowgill et al (2018) suggested that the closure of the basin initiated at about 35 My ago and ended at about 5 My ago following the collision between the Lesser Caucasus and the Scythian platform to form the Greater Caucasus. The basic underlying assumption related to the collision is that the Greater Caucasus results from farfield transmission of tectonic stresses from the Bitlis-Zagros collision zone.…”
Section: Geology and Geodynamicsmentioning
confidence: 99%
“…Vincent et al (2007), instead, related basin closure around the Eocene-Oligocene transition to the far-field effects of initial Arabia-Eurasia collision, with this process being unrelated to later Arabia-Eurasia reorganization. Further details of these contrasting hypotheses can be found in the papers cited above and the ensuing correspondence (Cowgill et al, 2018;Vincent et al, 2018). Shaded relief digital elevation model of the Arabia-Eurasia collision zone showing selected GPS-constrained motions relative to stable Eurasia, the occurrence of instrumentally recorded earthquakes (M ≥ 4.5) and a selected number of their focal mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Vincent et al (), instead, related basin closure around the Eocene‐Oligocene transition to the far‐field effects of initial Arabia‐Eurasia collision, with this process being unrelated to later Arabia‐Eurasia reorganization. Further details of these contrasting hypotheses can be found in the papers cited above and the ensuing correspondence (Cowgill et al, ; Vincent et al, ).…”
Section: Introductionmentioning
confidence: 99%